Scalable Cloud Computing Architecture for IoT Data Processing - Singh Kashyap, Vishal (Computational Engineering and Technology Innovations, 2024)
The Internet of Things (IoT) generates massive amounts of data that require efficient processing, storage, and analysis. The cloud provides the necessary infrastructure for handling these data streams at scale, enabling IoT systems to function seamlessly. However, scaling cloud resources for real-time IoT applications presents latency, cost management, security, and data integration challenges. This paper explores the architecture of scalable cloud computing systems for IoT data processing. We analyze key components such as load balancing, distributed computing, and serverless architectures. We also review case studies and technologies such as edge computing, 5G, and Machine Learning (ML) integration, which offer new opportunities for scalability. Finally, we highlight future trends in cloud computing and the growing importance of AI and blockchain in improving scalability and security.